Blunt to sharpened razor: incremental reform and distortions in the product and capital markets in China - Zhang, Xiaobo; Tan, Kong-Yam (International Food Policy Research Institute, 2004)
A key objective of China's reform program was to reduce distortions in the economic system and enhance growth. However, when implemented in incremental and partial ways, local governments or individuals have chance to capture rents inherent in the reform process. Young (2000) warned that the rent-seeking behavior might lead to increasing market fragmentation. Empirical studies have since shown that this did not happen in the product markets. In this paper we argue that as rents from the product markets were squeezed out during the reform process, rent-seeking behavior shifted to the factor markets, especially the capital and land markets. The reform process now needs to be deepened to ensure that the factor markets also become more integrated and efficient. -- Authors' Abstract